\Perancangan Sistem Pemesanan Menggunakan Framework Laravel dengan Metode Prototype (Studi Kasus: Moelly Cakes and Cookies) - Muhamad Zikra Hidayat Rusli; Heri Haerudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Understanding of the role of information technology in various aspects of human life has penetrated to all levels of society with the spread of the global internet. Today's internet network covers the entire world, allowing online access and interaction for various groups. One of the main ways to disseminate information is through websites, which facilitate and accelerate the dissemination of information about products and activities. However, the use of websites has evolved more than just as a tool for obtaining information. Currently, Moelly Cakes and Cookies has utilized the role of information technology in the form of Instagram and WhatsApp social media as an ordering system, but faces difficulties in collecting orders when orders come to increase, especially before holidays, this is because the owner has to respond to every incoming message from the mdisocial media customer which greatly hampers the owner's operational rate. Therefore, in this study, a booking system will be designed and implemented that makes it easier for business owners and customers to place orders. The method used is the prototype method. With this web-based ordering system, Moelly Cakes and Cookies can increase the efficiency and accuracy of order collection. Business owners can track orders, select products, manage payments, and arrange shipments easily. Customers also get a better ordering experience through an easy-to-use interface and complete product information. By using the Laravel framework, the development of cake ordering applications becomes more efficient. Laravel has many ready-to-use libraries and an active community, speeding up the development process. Based on the data obtained from the results of the calculation of questionnaire data, a percentage of 89% of 100% was obtained. Therefore, it can be concluded that this cake ordering website can already meet the goals and needs.